Global Village UMP promotes better command of English among secondary school students - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP), in collaboration with its Association of International Economic & Commercial Science Student Club (AIESEC), Department of Student Affairs & Alumni (JHEPA) and UMP International Office, recently organized a programme to promote better command of the English language among secondary school students.